“If I Died Tomorrow, I’d Die Knowing That My Son Is Safe, Loved by the People in Here, Well Cared for, and Happy”: Exploring Maternal Perspectives on Community Living for Their Adult Children with Intellectual and Developmental Disabilities - Margherita Cameranesi; Maria Baranowski; Lindsay McCombe; Kayla Kostal; Javier Mignone; Shahin Shooshtari (Disabilities)
There is abundant evidence that, following community transition or deinstitutionalization, persons with intellectual and developmental disabilities experience improvements in quality of life and well-being. However, very little research in this area has been conducted in the Canadian context. In this qualitative study, individual in-depth interviewing was used to explore the perspectives of eight Canadian mothers of adults with intellectual and developmental disabilities regarding their children’s residences and access to services after community transition. Within an interpretive description framework, narrative data collected during semi-structured interviews with participating mothers were analyzed using thematic analysis. Three main themes portraying a combination of positive and negative maternal perspectives emerged from the data: (1) quality of care, (2) quality of life, and (3) health status and behavior. The study findings bring attention to the importance of offering individualized community living options that are person- and family-centered to all persons with intellectual and developmental disabilities.